Clinical approach to auditory malingering in an adolescent - Yasin, Fikry; Zizlavsky, Semiramis; Irfan, Irfan; Kaligis, Fransiska (PERHATI-KL, 2024)
Background: Cases of auditory malingering are frequently encountered in medical practice, but there was very limited scientific evidence on the characterization of auditory malingering in children and adolescents. Purpose: To provide a comprehensive description of an auditory malingering case in an adolescent. Case Report: A 14-year-old boy came with complaints of sudden bilateral deafness, for the last three months. Hearing examination findings were within normal limits. Discussion: An objective hearing examination was necessary to complement subjective assessments in establishing the diagnosis of hearing loss. In this case, following normal auditory findings and subsequent consultations, the patient admitted that he had feigned his symptoms to avoid bullying by his friends, who mocked him for never having visited Jakarta. Conclusion: The examination of hearing function should involve not only subjective hearing examinations, but also objective hearing examinations to establish a diagnosis of hearing loss. Keywords: hearing loss, hearing examination, malingering ABSTRAK Latar belakang: Kasus malingering yang melibatkan organ pendengaran cukup sering ditemukan dalam praktek kedokteran sehari-hari, namun bukti ilmiah yang mendeskripsikan kejadian malingering pendengaran pada anak-anak dan remaja masih sangat terbatas. Tujuan: Untuk menyampaikan secara komprehensif suatu kasus malingering pendengaran pada seorang remaja. Kasus: Laki-laki usia 14 tahun datang dengan keluhan mendadak tidak dapat mendengar pada kedua telinga sejak 3 bulan terakhir. Hasil pemeriksaan fungsi pendengaran dalam batas normal. Pembahasan: Pemeriksaan fungsi pendengaran secara obyektif diperlukan untuk menegakkan diagnosis gangguan pendengaran. Pada kasus ini, setelah temuan pendengaran yang normal dan konsultasi lanjutan, pasien mengaku telah memalsukan gejalanya untuk menghindari perundungan teman-temannya yang mengejeknya karena belum pernah mengunjungi Jakarta. Kesimpulan: Pemeriksaan fungsi pendengaran sebaiknya tidak hanya dilakukan pemeriksaan pendengaran subyektif saja, namun diperlukan juga pemeriksaan pendengaran obyektif untuk menegakkan diagnosis gangguan pendengaran. Kata kunci: gangguan pendengaran, pemeriksaan fungsi pendengaran, malingering